Suitability of the milk of native breeds of cows from low‐input farms for cheese production, including rennet curd texture. (27th May 2016) - Wolanciuk, Anna; Barłowska, Joanna; Litwińczuk, Zygmunt; Florek, Mariusz
Abstract : The cheesemaking suitability of the milk of native cow breeds [Polish Red (RP) and White‐Backed (BG)] raised on low‐input farms was assessed. The milk of Polish Holstein‐Friesian cows raised in an intensive system constituted the reference group. Chemical composition, pH, rennet coagulation time, fat dispersion and curd texture were determined. The cows on the low‐input farms produced over 40% less milk, but with higher ( P ≤ 0.01) fat content, shorter coagulation time by over 2 min and lower ( P ≤ 0.05) fat dispersion. The curds from this milk were significantly springier, more cohesive and harder. The best milk indices were obtained for the RP cows.